HUBUNGAN TERPAAN KAMPANYE #WEAREMORE DAN TERPAAN ONLINE CUSTOMER REVIEW PADA KOLOM KOMENTAR INSTAGRAM @Myxl TERHADAP LOYALITAS PELANGGAN XL - Putri Febrianti; Yanuar Luqman; Djoko Setyabudi (Interaksi Online, 2023)
XL is a company engaged in cellular telecommunication which was founded on October 6, 1989 with the initial name PT Grahametropolitan Lestari. XL has done many ways to carry out sales promotions, one of which is through the #WeAreMore campaign. On the other hand, XL also conducts sales promotions through Instagram @Myxl. Currently, Instagram @Myxl has 218k followers. On instagram @Myxl, you can often see bad or good reviews about the performance of the XL brand. Therefore, this study aims to determine the correlation between #WeAreMore campaign exposure and online customer review (0CR) exposure to XL customer loyalty. This study uses the theory of Behavioral Learning and Social Cognitive Theory, the sample is 100 respondents with age criteria 18 - 34 years who have seen the #WeAreMore campaign and follow instagram @Myxl. This research uses non-probability sampling with accidental sampling technique.  This study looks at the results of the significance value between the #WeAreMore campaign exposure to XL Customer Loyalty of 0.000. These results are said to be significant if the results obtained have a significance value of <0.05 and a pearson product moment correlation coefficient of 0.376, which means that the two variables have a weak and positive relationship. This means that if exposure to the #WeAreMore campaign increases, then XL’s customer loyalty level also increases. Then, in the second hypothesis correlation test, there is a positive relationship in the instargam @Myxl comments column and XL customer loyalty showing a significance value of 0.000. These results also show a significant and pearson product moment correlation coefficient value of 0.431, which means that the two variables have a moderate and positive relationship. This means that if the Online Customer Reviews in the @Myxl Instagram comment column have increased, then XL customer loyalty has also increased